Knowledge Asymmetry in Action - Ushma Chauhan Jacobsen (Hermes, 2014)
This article forges a connection between knowledge asymmetry and intercultural communication to challenge extant understandings of knowledge asymmetry as a static and stable condition that infl uences the processes and outcomes of interactive encounters that promote learning. The article draws its empirical material from ethnographic fieldwork at a training course on climate change that involved the participation of development practitioners, policy makers and civil servants working in broad professional arenas such as engineering, agriculture, water management and urban development in Sri Lanka, Kenya, Egypt, Bangladesh, Uganda, Tanzania, Vietnam and Denmark. The material is represented in the form of ethnographic vignettes to demonstrate knowledge asymmetry ‘in action’: how knowledge asymmetry is far from a static and stable condition, but rather how it emerges and disappears as participants summon, articulate, dismiss, ridicule, ignore or explore the rich pools of their culture/knowledge differences during the training course interaction. The article aligns itself to Barth’s (2002) conceptualization of culture as knowledge and to contemporary understandings of intercultural communication that privilege sensitivities to the webs of geo-historical relations and macro power and economic asymmetries that structure and inform intercultural relationships. The article also emphasizes the relevance of seeing knowledge asymmetry as a concept-metaphor (Moore 2004).